Adaptasi Anatomis Tumbuhan Terhadap Perbedaan Stress Lingkungan - Hafidha Asni Akmalia (FMIPA : Universitas PGRI Adi Buana, 2021)
Adaptations are carried out by plants for their survival in a very dynamic environment. An example of adaptation that has been developed is anatomical adaptation in root, stem and leaves. The purpose of this review article is to provide steps that humans can take in helping plants to maintain their anatomical adaptations so that they can promote plant growth and development under environmental stress. This review is based on a literature review of scientific articles that discuss the anatomical adaptation of plants to different environmental stresses. Based on the studies conducted, further research efforts are needed to keep plants sustainable under increasingly challenging environmental stress. Keywords: adaptation; anatomy; environmental stress